A fatal inheritance : how a family misfortune revealed a deadly medical mystery - Ingrassia, Lawrence (Henry Holt and Company, 2024)
"Weaving his own moving family story with this sweeping history of cancer research, Lawrence Ingrassia delivers an intimate, gripping tale that sits at the intersection of memoir and medical thriller"--